Anion-cation high-entropy doped lithium-rich manganese-based positive electrode material and preparation thereof, and battery based on material
Through the high entropy doping strategy of anion and cation, the transition metal position and oxygen position are occupied, and the problems of poor cyclic stability and rate performance of lithium-rich manganese-based positive electrode materials are solved, which significantly improves the structural stability and capacity retention rate of the material, and achieves the realization of the material. More efficient electrochemical properties.
Patent Information
- Application Number
- CN202411294485.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
Smart Images

Figure CN119170798A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-rich manganese-based positive electrode materials, and in particular to lithium-rich manganese-based positive electrode materials doped with high entropy of anions and cations, and preparation thereof, and batteries based on the materials. Background Art
[0002] Lithium-rich manganese-based cathode material xLi2MnO 3· (1-x)LiMO2 (M is a transition metal, 0≤x≤1) is a composite material composed of layered LiMO2 and Li2MnO3. The material introduces the Li2MnO3 phase on the basis of the layered material, which not only improves the stability of the layered LiMO2 structure under high pressure, but also can release more active Li when charged to above 4.5V, thus having a higher specific capacity (greater than 300mAh / g). Although lithium-rich manganese-based materials have a high specific capacity, there are still some problems in their actual application, such as high irreversible capacity in the first cycle, poor rate performance, and poor cycle stability caused by the transformation of the layered structure to the spinel structure during the cycle, which has prevented the material from being well applied. The existing modification methods for lithium-rich manganese-based materials mainly include: ① Surface coating, by coating a layer of oxide, fluoride, etc. on the surface of lithium-rich manganese-based materials to inhibit the dissolution of transition metals and the occurrence of surface side reactions, thereby improving their cycle stability, but the coating material itself is usually an electrochemically inert substance, coating it on the surface often leads to capacity loss, and it is difficult to obtain a coating phase with uniform thickness during the actual preparation process, thereby affecting the overall performance of the material; ② Doping modification, by doping cations such as Al, Mg, Ti, Cr, Ru or doping anions such as F, S to enhance the bonding strength between transition metals and oxygen to improve oxygen stability, thereby improving the thermal stability and structural stability of the material. Doping modification is currently the most widely used and effective modification method, but different doping elements have different effects on electrode materials, and it is necessary to optimize the selection of dopants and doping concentrations. ③ Surface modification treatment, such as acid treatment of the material surface, removes part of Li, and transforms the surface layered structure into a spinel structure, thereby improving the rate performance of Li ions, but the surface treatment method is cumbersome and there is a problem of incompatibility with existing production lines.
[0003] In recent years, high entropy materials have attracted widespread attention in various fields. High entropy materials are composed of five or more elements in a nearly equimolar ratio. The presence of multiple elements can interact with each other to produce a synergistic effect and improve the performance of the material. High entropy materials have a series of excellent properties such as high hardness, good structural stability, and good corrosion resistance. Since the main elements of existing positive electrode materials are Ni, Co, and Mn, the concept of high entropy is applied to positive electrode materials, usually by doping multiple elements, and the doping amount of each element is generally controlled below 2 mol%. Chinese patents CN115513449A and CN117712339A respectively announced methods for modifying lithium-rich manganese-based positive electrode materials using high entropy doping strategies, thereby improving their cycle stability and rate performance. However, both methods only use cation high entropy doping. Most of these cations will occupy transition metal positions after doping, and some element doping will also occupy Li positions. There are also anion positions in lithium-rich manganese-based materials, and doping at the anion position can further exert the entropy increase effect of high entropy materials. According to previous research results, anion doping such as F, Cl, S, Br, and I will occupy the O position. When combined with cation doping, the high-entropy lithium-rich manganese-based material structure obtained by this anion-cation high-entropy doping strategy will be more stable, which can avoid the large-scale release of oxygen during the first cycle of charging and discharging, as well as the continuous decay of voltage and capacity during the cycle. Summary of the invention
[0004] The purpose of the present application is to provide a lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, and its preparation, as well as a battery based on the material, to further enhance the configurational entropy through high entropy co-doping of anions and cations, and to enhance the improvement of structural stability by the high entropy doping strategy.
[0005] The present application discloses a lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, characterized in that the chemical formula of the lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations is Li 1.2 Ni x Mn y A 0.8-x-y O z B 2-z , wherein A is at least four of Al, Ti, Mg, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ru, Sn, Sb, Te, Ta, W, Se, Ce, and Co, B is at least one of F, Cl, S, Br, and I, and 0.4≤x+y<0.8.
[0006] The method for preparing the above-mentioned anion and cation high entropy doped lithium-rich manganese-based positive electrode material comprises the following steps:
[0007] Step 1: Grind and mix NiO powder, MnO2 powder, Li-containing compound powder, A-containing compound powder and B-containing compound powder according to chemical ratio to obtain a mixture;
[0008] Step 2: The mixture obtained in step 1 is subjected to two-stage calcination to obtain the target anion and cation high entropy doped layered lithium-rich manganese-based positive electrode material.
[0009] Preferably, in step 2, the specific steps of the second-stage calcination are to calcine the mixture obtained in step 1 at 350-650°C for 4-10h, and then heat it to 750-950°C and keep it for 8-20h, wherein the heating rate is 5°C / min and the cooling rate is 2°C / min, to obtain an anion and cation high entropy doped layered lithium-rich manganese-based positive electrode material.
[0010] Preferably, in step one, the Li-containing compound powder is Li2CO3, the A-containing compound is at least four of Al2O3, Ti2O3, Nb2O5, MgO, V2O5, Cr2O3, Fe2O3, CuO, ZnO, ZrO2, Nb2O5, MoO2, RuO4, SnO2, Sb2O3, TeO2, Ta2O5, WO3, SeO2, CeO2, and Co2O3, and the B-containing compound is at least one of NH4F, LiCl, MnS, NiBr, and LiI.
[0011] The present application also provides a battery comprising the above-mentioned lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, wherein the lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, Super P and PVDF are mixed in a mass ratio of 8:1:1 to form a positive electrode sheet, lithium metal is used as the negative electrode, Celgard 2400 is used as the diaphragm, and 1M LiPF6 EC / DMC solution is used as the electrolyte, and a CR2025 button battery is assembled in a glove box filled with argon.
[0012] Preferably, the steps for preparing the positive electrode plate are: mixing the lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, SuperP and PVDF in a mass ratio of 8:1:1 to form a positive electrode slurry, then coating the positive electrode slurry on aluminum foil, drying the coated electrode plate in a vacuum oven and cutting it to obtain the final positive electrode plate.
[0013] Preferably, the volume ratio of EC to DMC is 1:1.
[0014] Therefore, the present application adopts the above-mentioned anion and cation high entropy doped lithium-rich manganese-based positive electrode material and the preparation and battery based on the material, which has the following beneficial effects:
[0015] 1. In the present application, type A cations are doped to occupy transition metal sites or lithium sites, and type B anions are doped to occupy O sites. This high-entropy doping strategy of anions and cations can further exert the high-entropy effect and improve the structural stability of high-entropy cathode materials.
[0016] 2. High entropy doping can not only improve the electronic conductivity of lithium-rich manganese-based materials, but also expand the (003) crystal plane spacing, which is helpful for Li + Rapid transportation.
[0017] 3. Since the binding ability of the doped elements with oxygen is higher than that of Ni and Mn with oxygen, the stability of the material during the cycle can be improved. At the same time, the binding ability of the doped anions with transition metals is also stronger than that of oxygen with transition metals, which can further improve the stability of the material during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an X-ray diffractometer result diagram of the lithium-rich manganese-based positive electrode material obtained in Example 1 of the present application;
[0019] Figure 2 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present application;
[0020] Figure 3 This is a cycle-discharge capacity diagram of the battery prepared in Comparative Example 2 of the present application;
[0021] Figure 4 This is a cycle-discharge capacity diagram of the battery prepared in Example 2 of the present application;
[0022] Figure 5 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present application;
[0023] Figure 6 This is a cycle-discharge capacity diagram of the battery prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0024] The chemical formula of the lithium-rich manganese-based positive electrode material doped with anions and cations in this application is Li 1.2 Ni x Mn y A 0.8-x- y O z B 2-z , wherein A is at least four of Al, Ti, Mg, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ru, Sn, Sb, Te, Ta, W, Se, Ce, and Co, and their contents are represented by a1, a2, a3, ai…an1, respectively (n1≥4); the number B is at least one of F, Cl, S, Br, and I, and their contents are represented by b1, b2, bi…bn2, respectively (n2≥1); 0.4≤x+y<0.8, 0 <ai≤0.1, 1.5≤z<2,0 <bi≤0.1, And meet
[0025] Example 1
[0026] The chemical formula of the synthesized positive electrode material is Li 1.2 Mn 0.4 Ni 0.16 Te 0.06 Al 0.0.06 Mg 0.06 Nb 0.06 F 0.06 O 1.94 , take NiO1.356g, MnO23.944g, TeO21.086g, Al2O30.347g, MgO0.274g, Nb2O50.904g, Li2CO35.027g and NH4F0.252g powders and grind and mix them evenly, heat them to 500℃ at a rate of 5℃ / min in air atmosphere, keep them warm for 5h, heat them to 900℃ at a rate of 5℃ / min, keep them warm for 15h, and then cool them to room temperature at a cooling rate of 2℃ / min to obtain anion-cation high entropy doped layered lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.4 Ni 0.16 Te 0.06 Al 0.0.06 Mg 0.06 Nb 0.06 F 0.06 O 1.94 The calculated entropy value of the cathode material is 1.792R, which is greater than 1.609R and belongs to the category of high entropy materials.
[0027] The X-ray diffractometer results of the lithium-rich manganese-based positive electrode material prepared by the above method are as follows: Figure 1 As shown in the figure, it can be seen that the material belongs to α-NaFeO2 structure and has good crystallinity. Figure 2 This is a scanning electron microscope image of the prepared lithium-rich manganese-based positive electrode material.
[0028] The prepared lithium-rich manganese-based positive electrode material, Super P and PVDF were mixed evenly in a mass ratio of 8:1:1, NMP was used as a solvent, and the positive electrode slurry was obtained by stirring for more than 6 hours, which was then coated on aluminum foil, and the coated electrode was baked in a vacuum oven for 12 hours at a temperature of 80°C. The dried electrode was cut into a positive electrode electrode with a diameter of 12 mm, lithium metal was used as the negative electrode, Celgard 2400 was used as a diaphragm, and 1M LiP F6 EC / DMC (volume ratio 1:1) solution was used as an electrolyte, and a CR2025 button battery was assembled in an argon-filled glove box, which is the battery of Example 1. The battery of Example 1 was tested at a voltage of 2.0-4.8V, and constant current charge and discharge was performed at a current of 125mA / g. The discharge capacity of the first cycle was 264.56mAh / g, the reversible discharge capacity of the 100th cycle was 258.2mAh / g, and the capacity retention rate was 97.6%.
[0029] Example 2
[0030] The chemical formula of the synthesized positive electrode material is Li 1.2 Mn 0.4 Ni 0.18 Ti 0.055 Nb 0.055 Mg 0.055 Fe 0.055 I 0.06 O 1.94 , take NiO2.132g, MnO24.770g, Ti2O30.079g, Nb2O50.146g, MgO0.044g, Fe2O30.087g, Li2CO34.718g powders and grind and mix them evenly, heat to 500℃ at a rate of 5℃ / min in air atmosphere, keep warm for 5h, heat to 880℃ at a rate of 5℃ / min, keep warm for 15h, and then cool to room temperature at a cooling rate of 2℃ / min to obtain anion-cation high entropy doped layered lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.4 Ni 0.18 Ti 0.055 Nb 0.055 Mg 0.055 Fe 0.055 I 0.06 O 1.94 The calculated entropy value of the cathode material is 1.770R, which is greater than 1.609R and belongs to the category of high entropy materials.
[0031] The prepared positive electrode material, lithium-rich manganese-based positive electrode material, Super P and PVDF were mixed uniformly in a mass ratio of 8:1:1, and NMP was used as a solvent. The positive electrode slurry was stirred for more than 6 hours, and then coated on aluminum foil. The coated electrode was baked in a vacuum oven for 12 hours at a temperature of 80°C. The dried electrode was cut into a positive electrode with a diameter of 12 mm, and lithium metal was used as the negative electrode, Celgard 2400 was used as a separator, and 1M Li PF6 EC / DMC (volume ratio 1:1) solution was used as an electrolyte. CR 2025 button batteries were assembled in a glove box filled with argon, which is the battery of Example 2. Figure 4 This is the long cycle curve of the battery of Example 2. The battery of Example 2 was tested at a voltage of 2.0-4.8V, and constant current charge and discharge were performed at a current of 125mA / g. The first cycle discharge capacity was 278.37mAh / g, the reversible discharge capacity of the 100th cycle was 259.7mAh / g, and the capacity retention rate was 93.3%.
[0032] Comparative Example 1
[0033] The chemical formula of the synthesized positive electrode material is Li 1.2 Mn 0.4 Ni 0.16 Te 0.06 Al 0.0.06 Mg 0.06 Nb 0.06 Take NiO1.358g, MnO23.952g, TeO21.088g, Al2O30.348g, MgO0.275g, Nb2O50.906g, Li2CO35.037g and NH4F0.252g powders, grind and mix them evenly, heat to 500℃ at a rate of 5℃ / min in air atmosphere, keep warm for 5h, heat to 900℃ at a rate of 5℃ / min, keep warm for 15h, and then cool to room temperature at a cooling rate of 2℃ / min to obtain anion-cation high entropy doped layered lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.4 Ni 0.16 Te 0.06 Al 0.0.06 Mg 0.06 Nb 0.06 O2. The calculated entropy value of the positive electrode material is 1.657R, which is greater than 1.609R and belongs to the category of high entropy materials. Figure 5 Scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1
[0034] The prepared lithium-rich manganese-based positive electrode material, Super P and PVDF were mixed evenly in a mass ratio of 8:1:1, and NMP was used as a solvent. The positive electrode slurry was obtained by stirring for more than 6 hours, and then coated on aluminum foil. The coated electrode was dried in a vacuum oven for 12 hours at a temperature of 80°C. The dried electrode was cut into a positive electrode with a diameter of 12 mm, and lithium metal was used as the negative electrode, Celgard 2400 was used as a separator, and 1M LiP F6 EC / DMC (volume ratio 1:1) solution was used as an electrolyte. The CR2025 button battery was assembled in a glove box filled with argon, which is the battery of comparative example 1. Figure 6 This is the long cycle curve of the battery of Example 1. The battery of Example 1 was tested at a voltage of 2.0-4.8V, and constant current charge and discharge were performed at a current of 125mA / g. The first cycle discharge capacity was 250.65mAh / g, the reversible discharge capacity of the 100th cycle was 230.98mAh / g, and the capacity retention rate was 92.2%.
[0035] Comparative Example 2
[0036] The chemical formula of the synthesized positive electrode material is Li 1.2 Mn 0.4 Ni 0.18 Ti 0.055 Nb 0.055 Mg 0.055 Fe 0.05 O2, take NiO2.300g, MnO25.146g, Ti2O30.085g, Nb2O50.157g, MgO0.047g, Fe2O30.094g, Li2CO35.248g powders and grind and mix them evenly, heat them to 500℃ at a rate of 5℃ / min in air atmosphere, keep them warm for 5h, heat them to 880℃ at a rate of 5℃ / min, keep them warm for 15h, and then cool them to room temperature at a cooling rate of 2℃ / min to obtain a layered lithium-rich manganese-based positive electrode material Li with only cation high entropy doping. 1.2 Mn 0.4 Ni 0.18 Ti 0.055 Nb 0.055 Mg 0.055 Fe 0.05 O2. The calculated entropy value of the positive electrode material is 1.635R, which is greater than 1.609R and belongs to the category of high entropy materials.
[0037] The prepared positive electrode material, lithium-rich manganese-based positive electrode material, Super P and PVDF were mixed evenly in a mass ratio of 8:1:1, and NMP was used as a solvent. The positive electrode slurry was obtained by stirring for more than 6 hours, and then coated on aluminum foil. The coated electrode was baked in a vacuum oven for 12 hours at a temperature of 80°C. The dried electrode was cut into a positive electrode with a diameter of 12 mm, and lithium metal was used as the negative electrode, Celgard 2400 was used as a separator, and 1M Li PF6 EC / DMC (volume ratio 1:1) solution was used as the electrolyte. The CR 2025 button battery was assembled in a glove box filled with argon, which is the battery of comparative example 2. Figure 3 This is the long cycle curve of the battery of Example 2. The battery of Example 2 was tested at a voltage of 2.0-4.8V, and constant current charge and discharge were performed at a current of 125mA / g. The first cycle discharge capacity was 253.77mAh / g, the reversible discharge capacity of the 100th cycle was 170.32mAh / g, and the capacity retention rate was 67.1%.
[0038] Therefore, the present application provides a lithium-rich manganese-based positive electrode material doped with anions and cations with high entropy, and a preparation and a battery based on the material. On the basis of cation doping, the present invention further introduces the doping of anions at the O position. This anion and cation high entropy doping strategy can further improve the structural stability and reduce the capacity decay and voltage hysteresis during the cycle. The preparation process of this method is simple and easy to match with the existing process. Through the co-doping of anions and cations, the configuration entropy is further enhanced, and the improvement of the structural stability by the high entropy doping strategy is enhanced.
[0039] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0040] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, characterized in that: The chemical formula of the lithium-rich manganese-based cathode material doped with high entropy of anions and cations is Li 1.2 Ni x Mn y A 0.8-x-y O z B 2-z , wherein A is at least four of Al, Ti, Mg, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ru, Sn, Sb, Te, Ta, W, Se, Ce, and Co, B is at least one of F, Cl, S, Br, and I, and 0.4≤x+y<0.
8.
2. The method for preparing a lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations according to claim 1, characterized in that: The following steps are involved: Step 1: Grind and mix NiO powder, MnO2 powder, Li-containing compound powder, A-containing compound powder and B-containing compound powder according to a chemical ratio to obtain a mixture; Step 2: The mixture obtained in step 1 is subjected to two-stage calcination to obtain the target anion and cation high entropy doped lithium-rich manganese-based positive electrode material.
3. The method for preparing a lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations according to claim 1, characterized in that: In step 2, the specific steps of the second-stage calcination are to calcine the mixture obtained in step 1 at 350-650°C for 4-10h, and then heat it to 750-950°C and keep it for 8-20h, wherein the heating rate is 5°C / min and the cooling rate is 2°C / min, to obtain a lithium-rich manganese-based positive electrode material doped with anions and cations with high entropy.
4. The lithium-rich manganese-based positive electrode material doped with anions and cations with high entropy according to claim 3, characterized in that: In step 1, the Li-containing compound powder is Li2CO3, the A-containing compound is at least four of Al2O3, Ti2O3, Nb2O5, MgO, V2O5, Cr2O3, Fe2O3, CuO, ZnO, ZrO2, Nb2O5, MoO2, RuO4, SnO2, Sb2O3, TeO2, Ta2O5, WO3, SeO2, CeO2, and Co2O3, and the B-containing compound is at least one of NH4F, LiCl, MnS, NiBr, and LiI.
5. A battery, characterized in that: The invention comprises the lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations as described in claim 1, wherein the lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, Super P and PVDF are mixed in a mass ratio of 8:1:1 to form a positive electrode sheet, lithium metal is used as a negative electrode, Celgard 2400 is used as a diaphragm, and 1M LiPF6 EC / DMC solution is used as an electrolyte, and a CR2025 button battery is assembled in a glove box filled with argon.
6. A battery according to claim 5, characterized in that: The steps for preparing the positive electrode plate are as follows: the lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations, Super P and PVDF are mixed in a mass ratio of 8:1:1 to form a positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil, and the coated electrode plate is dried in a vacuum oven and cut to obtain the final positive electrode plate.
7. The lithium-rich manganese-based positive electrode material doped with high entropy of anions and cations according to claim 1, characterized in that: The volume ratio of EC to DMC was 1:1.
Citation Information
Patent Citations
Negative and positive ion co-doped modified lithium ion battery positive material and preparation method thereof
CN110323432A
High-entropy positive electrode material and preparation method and application thereof
CN113003615A
Single crystal type high-entropy lithium-rich positive electrode material, preparation method and application thereof
CN116979060A
O3-type high-entropy layered manganese-based sodium-ion battery positive electrode material and preparation method and application thereof
CN117088416A
Lithium-rich manganese-based positive electrode material and preparation method and application thereof
CN117976863A
Cited By
Lithium-rich manganese-based positive electrode material and preparation method thereof, positive plate, lithium ion battery and power-related equipment
CN119481032A
Lithium ion positive electrode material doped with tin ions and fluorine ions and preparation method of lithium ion positive electrode material
CN121885607A
